CRYSTAL STRUCTURE ANALYSIS OF CuCrO2 BASED ON XRD DATA USING GSAS SOFTWARE - Didik, Lalu A.; Wahyudi, Muh. (Universitas Mataram, 2021)
The synthesis of CuCrO2 crystals by mixing CuO and Cr2O3 has been carried out using the solid reaction method at a temperature of 1200 0C. The characterization of the structure used XRD and analyzed using GSAS software. The results of characterization using XRD showed that no other phase occurred. This is evidenced by the absence of other phases from the results of refinement of measurement data with reference data and a value of χ 2 which is 1.222. The lattice parameter values resulting from the refinement of the CuCrO2 X-ray diffraction pattern are a = b = 2.9715 Å and c = 17.1104 Å with a cell volume of 130.584 Å 3. In addition to the lattice parameter values, the distance between atoms was also obtained, both Cu - O, Cr - Cr, and Cr - O.